2021
DOI: 10.2147/rmhp.s314487
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index as a Prognostic Factor for Mortality in Elderly Patients with Moderate to Severe Traumatic Brain Injuries

Abstract: Background The Geriatric Nutritional Risk Index (GNRI) is a simple and objective screening tool for clinicians to screen patients’ nutritional status based on serum albumin level and their weight and height. The original study had divided patients based on GNRI into quartiles of nutritional risk for death: a no-risk group (GNRI >98), a low-risk group (GNRI 92–98), a moderate-risk group (GNRI 82 to <92), and a major-risk group (GNRI <82). Given that the patients generally sustained traumatic brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Prior studies using GNRI in trauma patients have demonstrated an association between GNRI and adverse clinical outcomes in geriatric trauma patients. Su et al 33 found an independent association between GNRI and mortality in geriatric patients with moderate to severe traumatic brain injury. Other studies corroborated this association between malnutrition and mortality as well as found an association between GNRI, prolonged hospital LOS, and poor functional outcomes 12,14,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies using GNRI in trauma patients have demonstrated an association between GNRI and adverse clinical outcomes in geriatric trauma patients. Su et al 33 found an independent association between GNRI and mortality in geriatric patients with moderate to severe traumatic brain injury. Other studies corroborated this association between malnutrition and mortality as well as found an association between GNRI, prolonged hospital LOS, and poor functional outcomes 12,14,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Kregel et al also identified that a low GNRI was associated with high mortality and increased infectious complaints among geriatric trauma patients ( 34 ). Moreover, the GNRI was identified to have satisfactory performance in predicting the clinical outcome of elderly severe TBI patients as well ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The geriatric nutritional risk index (GNRI), calculated by actual weight, ideal weight, and serum albumin concentration, is a simple and accurate index that reflects the nutritional condition of elderly patients ( 14 , 15 ). Furthermore, Su et al identified that GNRI was also correlated with the clinical outcome of geriatric patients suffering from moderate to severe TBI ( 16 ). However, the correlation between the GNRI and the clinical outcome of elderly mTBI patients is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric patients with TBI, on average, experience higher mortality and morbidity rates, slower recovery, and worse outcomes than younger patients [ 63 ]. A previous study showed that the Geriatric Nutritional Risk Index is a significant independent risk factor for mortality in geriatric patients with moderate to severe TBI [ 64 ]. Although malnutrition is closely related to poor outcomes during hospitalization in geriatric patients, it remains common and underdiagnosed [ 65 ].…”
Section: Unresolved Issues and Future Research Directionsmentioning
confidence: 99%